2011
DOI: 10.1016/j.biomaterials.2011.03.053
|View full text |Cite
|
Sign up to set email alerts
|

Critical-size calvarial bone defects healing in a mouse model with silk scaffolds and SATB2-modified iPSCs

Abstract: Induced pluripotent stem cells (iPSCs) can differentiate into mineralizing cells and thus have a great potential in application in engineered bone substitutes with bioactive scaffolds in regeneration medicine. In the current study we characterized and demonstrated the pluripotency and osteogenic differentiation of mouse iPSCs. To enhance the osteogenic differentiation of iPSCs, we then transduced the iPSCs with the potent transcription factor, nuclear matrix protein SATB2. We observed that in SATB2-overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
114
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(121 citation statements)
references
References 56 publications
(63 reference statements)
6
114
0
Order By: Relevance
“…These data confirmed that miR-31 regulates Satb2 expression at the translational but not transcriptional level and that this mechanism is in effect during cell differentiation and cancer metastasis. Additionally, our data showed that the expression of Runx2, Opn and Ocn followed the same pattern as Satb2 protein expression, which is consistent with previous studies that have demonstrated that Satb2 gene delivery accelerates the expression of osteogenic specific genes (Runx2, Opn and Ocn) and promotes bone regeneration (Yan et al, 2011;Ye et al, 2011). Moreover, micro-CT showed that anti-miR-31 treatment significantly improved ossification in the calvarial model.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These data confirmed that miR-31 regulates Satb2 expression at the translational but not transcriptional level and that this mechanism is in effect during cell differentiation and cancer metastasis. Additionally, our data showed that the expression of Runx2, Opn and Ocn followed the same pattern as Satb2 protein expression, which is consistent with previous studies that have demonstrated that Satb2 gene delivery accelerates the expression of osteogenic specific genes (Runx2, Opn and Ocn) and promotes bone regeneration (Yan et al, 2011;Ye et al, 2011). Moreover, micro-CT showed that anti-miR-31 treatment significantly improved ossification in the calvarial model.…”
Section: Discussionsupporting
confidence: 80%
“…Genetic therapy to enhance bone regeneration has become one of the most active areas in bone tissue engineering (Ye et al, 2011;Zou et al, 2011a). In this study, we developed functional tissue-engineered bone by incorporating miR-31-modified BMSCs into PGS scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…57 RUNX2 and OSX are two important factors in the upward pathway and regulate the differentiation of ADSCs into osteoblasts. [58][59][60] RUNX2 is an indispensable transcription factor for stem cell differentiation and the osteoblast maturation process during both endochondral and intramembranous ossification. It is important to maintain the progenitors of the stem cells and make the cells differentiate into osteoblasts.…”
Section: Expression Of Osteogenic Genes In Vitromentioning
confidence: 99%
“…The size of the defect used in this study was considered to be a critical size since it would take around 7 months to repair the whole defect of the calvaria based on the calculation from the local bone formation activity although the previous literature show that a 4 mm diameter could be a marginal size of the defect 35, 36. This calculation was performed as shown below; the local bone formation activity, which shows the calcified bone area made in a day, was around 5 × 10 3  µm 2 in the GH carrier group as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%